Low-carbohydrate diets differing in carbohydrate restriction improve cardiometabolic and anthropometric markers in healthy adults: A randomised clinical trial - Harvey,Cliff J. d. C.; Schofield,Grant M.; Zinn,Caryn; Thornley,Simon J.; Crofts,Catherine; Merien,Fabrice L. R. (PeerJ, 2019)
Background Low-carbohydrate, high-fat (LCHF) diets are useful for treating a range of health conditions, but there is little research evaluating the degree of carbohydrate restriction on outcome measures. This study compares anthropometric and cardiometabolic outcomes between differing carbohydrate-restricted diets. Objective Our hypothesis was that moderate carbohydrate restriction is easier to maintain and more effective for improving cardiometabolic health markers than greater restriction. Design A total of 77 healthy participants were randomised to a very low-carbohydrate ketogenic diet (VLCKD), low-carbohydrate diet (LCD), or moderate-low carbohydrate diet (MCD), containing 5%, 15% and 25% total energy from carbohydrate, respectively, for 12-weeks. Anthropometric and metabolic health measures were taken at baseline and at 12 weeks. Using ANOVA, both within and between-group outcomes were analysed. Results Of 77 participants, 39 (51%) completed the study. In these completers overall, significant reductions in weight and body mass index occurred ((mean change) 3.7 kg/m2; 95% confidence limits (CL): 3.8, 1.8), along with increases in high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, (0.49 mmol/L; 95% CL; 0.06, 0.92; p = 0.03), and total cholesterol concentrations (0.11 mmol/L; 95% CL; 0.00, 0.23; p = 0.05). Triglyceride (TG) levels were reduced by 0.12 mmol/L (95% CL; −0.20, 0.02; p = 0.02). No significant changes occurred between groups. The largest improvements in high density lipoprotein cholesterol (HDL-c) and TG and anthropometric changes occurred for the VLCKD group. Conclusions Low-carbohydrate, high-fat diets have a positive effect on markers of health. Adherence to the allocation of carbohydrate was more easily achieved in MCD, and LCD groups compared to VLCKD and there were comparable improvements in weight loss and waist circumference and greater improvements in HDL-c and TG with greater carbohydrate restriction.
Keywords: Low-carbohydrate; Diet; Nutrition; Ketogenic; Adherence; Carbohydrate restriction; LCHF; Cardiometabolic health